2010
DOI: 10.1002/ir.365
|View full text |Cite
|
Sign up to set email alerts
|

Investing in the future: The importance of faculty mentoring in the development of students of color in STEM

Abstract: Underrepresented racial minority students often seek a high level of contact with professors of color, viewing them as role models and proof that success in higher education is possible (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 20 publications
4
84
0
Order By: Relevance
“…This initial search pointed us to a number of studies in STEM higher education more broadly (e.g., Brown 2002;Espinosa 2011;Griffin et al 2010;Harper and Newman 2010;Price 2010;Seymour 1995;Strayhorn 2010). Most of these studies focus on university level policies and factors that can contribute to broadening access into mathematics, and increasing achievements of students from underrepresented backgrounds.…”
Section: Identifying Equity Studies In the Literaturesupporting
confidence: 42%
See 1 more Smart Citation
“…This initial search pointed us to a number of studies in STEM higher education more broadly (e.g., Brown 2002;Espinosa 2011;Griffin et al 2010;Harper and Newman 2010;Price 2010;Seymour 1995;Strayhorn 2010). Most of these studies focus on university level policies and factors that can contribute to broadening access into mathematics, and increasing achievements of students from underrepresented backgrounds.…”
Section: Identifying Equity Studies In the Literaturesupporting
confidence: 42%
“…Most of these studies focus on university level policies and factors that can contribute to broadening access into mathematics, and increasing achievements of students from underrepresented backgrounds. For example, researchers have documented the positive impact undergraduate research experiences (Espinosa 2011;Strayhorn 2010) and strong faculty mentoring (Griffin et al 2010;Herzig 2004) on the success of students of color in STEM. We found a limited number of studies that focus on experiences of students from underrepresented groups in postsecondary mathematics.…”
Section: Identifying Equity Studies In the Literaturementioning
confidence: 45%
“…Mentorship is beneficial for all involved but can be particularly effective for underrepresented populations of students in STEM and agricultural sciences. Numerous studies have cited mentoring relationships as one of the most important factors retaining women, racial minorities, and first‐generation college students in STEM disciplines through graduation (Griffin et al, 2010). Mentoring becomes even more important to ensure success in advanced‐degree programs.…”
Section: Guidelines For Being An Effective Mentoring Partnermentioning
confidence: 99%
“…Faculty mentoring is particularly important for retaining women and URM students (Landefeld, 2009; Tsui, 2007). Griffin et al (2010) found that faculty mentoring was an important source of support for Black STEM professors throughout graduate school. In their study, the sample of seven Black STEM professors identified faculty members, advisors, and peers further along in their program as primary mentors when reflecting on their graduate school experience.…”
Section: Review Of the Literaturementioning
confidence: 99%